PEMANFAATAN SAMPAH MENJADI SUMBER ENERGI - Redaksi Tim Jurnal (Energi & Kelistrikan, 2016)
During this rubbish into a serious problem, especially in urban areas. Many piles of garbage on Disposal Temporary (TPS) in settlements, polluting the air and groundwater, and become a breeding ground for animals and bacteria carrying diseases. After days accumulate and rot in the polling stations, garbage transported to the final disposal (landfill). Dozens of garbage trucks passing through a public road, spreading the odor and can spread the disease. In the landfill is also only allowed to accumulate, mounting, polluting the air, contaminating groundwater on a wider scale.Organic waste is waste that can be experienced weathering (decomposition) and breaks down into materials that are smaller and do not smell (often referred to as compost). Waste Management pattern is still adhered to the old paradigm where the waste is still dianggapsebagai something useless, economically viable and very disgusting. This article will discuss a little about the impact of waste incineration, so the general public can understand.